Inland Excess Water Projection Based on Meteorological and Pedological Monitoring Data on a Study Area Located in the Southern Part of the Great Hungarian Plain - Barta, Károly (Journal of Environmental Geography, 2013)
The research investigated the process of excess water formation. Complex measurement stations were developed in order to determine the most important hydro-meteorological and soil factors contributing to the formation of excess water. The stations measure the amount of precipitation, evapotranspiration, evaporation from water surface, soil moisture in 3 different depths; soil temperature in 5 different depths; furthermore, soil water level. The study area is located in the southeastern part of Hungary, near Szeged, in the flood plain of Tisza and Maros with extremely clayey soils. The former soil data were completed by new soil survey to determine several soil parameters (e.g. bulk density, porosity, field capacity, saturated hydraulic conductivity). Infiltration was calculated from the measured parameters and water budget elements of bigger rainfall event were analyzed between March 2010 and August 2011. Genetic types of excess water can be separated based on the data.